Implementation of Management Information Systems at Janji Jiwa Coffee Shop in Medan Selayang City to Improve Customer Satisfaction - Muhammad Arif Lubis; Malinda Sari Sembiring; Ahmad Riyansyah; Chandra Sentosa (Journal Of Management Analytical and Solution (JoMAS), 2024)
Indonesia's coffee market has grown significantly in recent years, and a large number of coffee shops have opened up. In the face of fierce competition, the Janji Jiwa Coffee Shop in Medan, Selayang City, must strive to retain and grow its clientele. This research aims to determine the application of the Management Information System used to increase customer satisfaction at Janji Jiwa coffee shop. This research uses a quantitative approach with survey methods. Data was collected from 30 customers of Janji Jiwa Coffee Shop in Medan Selayang through a specially designed questionnaire. Data analysis was carried out using descriptive statistical methods and linear regression to test the relationship between SIM implementation and customer satisfaction. The final regression results indicate that the dependent variable, Consumer Satisfaction of Janji Jiwa Medan Coffee, Medan Selayang District, is significantly impacted (p < 0.05) by the independent variable, Management Information System. Customer satisfaction at the Janji Jiwa Coffee Shop in Medan Selayang has increased dramatically once SIM was implemented. These results suggest that coffee shops can enhance consumer loyalty and streamline their operations by implementing SIM.